Using chloroplast DNA to trace postglacial migration of oaks into Britain - Ferris, C.; Oliver, Richard; Davy, A.; Hewitt, G. (1995)
Postglacial migration is a major factor responsible for the patterns of genetic variation we see in natural populations. Fossil pollen data indicate that early postglacial colonists such as oak, were able to take both western and eastern migration routes into Britain. Analysis at a finer level is now permitted by the use of modern molecular techniques. A 13-bp duplication in the chloroplast tRNALeul intron occurs in natural populations of East Anglian oaks, but is not found in other parts of Britain or from mainland Europe. The distribution of this marker suggests that the mutation occurred either in southern England, or during migration from the mainland, and became fixed in a source population from which East Anglia was colonized. Planting of non-native trees for roadside boundaries and in the grounds of old houses and estates, explains the absence of the marker from some East Anglian oaks.